Accounting information communication in the digital age: A systematic literature review of current trends - Rika Henda Safitri; Emylia Yuniarti; Sindy Elisia Husna; Zakia Ramadhani (Journal of Multiperspectives on Accounting Literature, 2026)
Purpose - The processes of creating, processing, and disseminating accounting data to stakeholders have changed as a result of digital transformation. The purpose of this study is to identify the most popular styles of presenting accounting information in the digital age. Design/methodology/approach - This Systematic Literature Review (SLR), conducted in accordance with the PRISMA guidelines, analyzes publications from 2021 to 2025. Of the 309 articles identified through the Scopus, Web of Science, and Google Scholar databases, 10 credible and relevant articles were selected for the research topic: “accounting information communication in the digital age.” Findings - The implementation of ERP, cloud computing, blockchain, and AI enhances the quality, comparability, and transparency of accounting information, with effectiveness determined by governance readiness, institutional trust, and human resources, particularly among SMEs and the public sector in developing countries. Practical implications - A recommendation for future research aimed at gaining a more contextual and comprehensive understanding is to use a mixed-methods approach. Originality/value - The uniqueness of this study lies in its inclusion of an analysis aimed at developing an integrative model of digital transformation in the field of accounting that identifies governance readiness and institutional trust.